Burnout Syndrome and Intention to Leave: An Analysis of its Impact through a Systematic Review 2015-2025 - Gonzales, Yuri; Guevara-Delgado , Nelly; Alcahuaman, Jeny; Jiménez, Víctor; Osorio, Patricia (Journal of Ecohumanism, 2025)
This study analyzed the scientific literature on burnout and intention to leave work, using both bibliometric methods and systematic reviews. A search was conducted in the Scopus database, to include the period 2015-2025, and keywords such as “burnout syndrome” or “burnout” and “Intention to leave” were used. The search was filtered to include only open access studies and the analysis was limited without geographical restrictions. For the analysis, 24 bibliometric studies were selected, which were exported in Bibtex format and processed with Cran-R, which were evaluated using the PRISMA guide. The study delved into the relationship between keywords, authors, publication sources and other bibliometric indicators (such as the presence of DOI and the number of annual citations), highlighting the USA as the country with the highest publication rate, followed by Gresia, concluding that both the burnout phenomenon and the intention to leave work are closely related, highlighting that identifying its causes such as stress, work overload, among others, consequences and aggravating factors such as anxiety, emotional exhaustion, job dissatisfaction, is essential to implement effective organizational strategies, such as organizational support and resilience training, which improve job well-being and reduce professional abandonment.